Alteraciones electrocardiográficas y marcadores bioquímicos de necrosis miocardiaca en pacientes con sospecha de infarto agudo de miocardio del hospital Regional Isidro Ayora de la ciudad de Loja - Cuenca León, Alex Eduardo (2014)
The metabolic syndrome (MS) is defined as a constellation of abnormalities in human physiology that are as elements of risk in the development of type 2 diabetes mellitus and cardiovascular disease, diseases of great social and health impact due to its high prevalence, complications chronic and associated high mortality. By this descriptive, prospective study of cross section entitled "METABOLIC SYNDROME IN PATIENTS ATTENDING THE SERVICE OF OUTPATIENT HOSPITAL DAY ZAMORA" the same that has a universe of 942 people who are seen at the Department of Internal Medicine, the sample was selected taking into account those with visceral obesity who meet criteria for diagnosis of metabolic syndrome, both genders and age greater than 20 years, shaping them a sample of 60 patients meeting inclusion criteria. The diagnosis of MS was made according to the criteria of ALAD. The aim of this study is to determine the prevalence of metabolic syndrome in patients presenting to the hospital the day of Zamora, in relation to age and sex, comparing visceral obesity as determined by NCEP ATP III vs ALAD and determining factors risk as smoking and physical inactivity to the development of metabolic syndrome, with the following results: The prevalence of metabolic syndrome was 6.37%, being more frequent in males (68.34%) than females (31.66%), and prevalence among the 50-59 years of age (48, 30%); Waist circumference as diagnostic criteria for SM has more frequently according to the criteria set by the ALAD 100% compared to the NCEP ATP III criteria with 73.33%. A sedentary lifestyle was evident in 73.33 % of the population, and 45% of them consume snuff. Key words: Visceral obesity, diabetes mellitus, cardiovascular disease.